A review of the genus Limnocythere (Podocopida: Limnocytheridae) in the Pampean region (Argentina), with the description of a new species, Limnocythere cusminskyae sp. nov. - Ramón-Mercau, Josefina; Plastani, María Sofía; Laprida, Cecilia (Zootaxa, 2014)
Occurrences of Quaternary and extant limnocytherids in the Pampean region of Argentina are reviewed, particularly in relation with their use as paleohydrological indicators in environmental reconstruction research. In spite of its spread occurrence, the systematic of the genus in the area is still little known, which results in most records being left in open nomenclature and paleoenvironmental inferences being made on the basis of general considerations of the genus. We describe a new species, Limnocythere cusminskyae sp. nov., which we consider to be the taxon featured in several of these works, and discuss its morphological and ecological differences with coexisting Limnocythere species, particularly the proposed indicator species L. rionegroensis Cusminsky & Whatley.